Identitas Diri Perempuan Novel Bilangan Fu Karya Ayu Utami: Kajian Ginokritik serta Implikasi Pendidikan Karakter - Rina Wulandari; Amril Amir (Universitas Mulawarman, 2023)
This research is motivated by the phenomenon of subordination from male authors towards women. Male authors only describe women's self-identity based on their point of view, while female authors can reveal everything based on their experiences. This research aims to describe the forms of women's self-identity in their appearance in the novel “Bilangan Fu” by Ayu Utami in gynocritical studies and is associated with its implications in character education. Data collection techniques are carried out using documentation techniques, reading, understanding, and classifying the entire novel that supports gynocritical analysis and character education values. Based on the findings and analysis in the novel “Bilangan Fu” by Ayu Utami regarding the forms of women's self-identity in their appearance. Body appearance has implications for the value of tolerance character education; patriarchal resistance has implications for democratic character education values; gender protests have implications for the value of attitude and behavior character education; and sexuality has implications for the value of honesty character education.